Perspective Owner Pada Enterprise Architecture Menggunakan Zachman Di Perusahaan Distributor Mesin - Rahman, Muhammad Ryo; Andry, Johanes Fernandes; Lee, Francka Sakti (Infotek: Jurnal Informatika dan Teknologi, 2025)
Machinery distributor companies have an important role in the industrial supply chain, where organizations are faced with various challenges, such as the possibility of stock management which is vulnerable to data errors and operational losses. This can result in operational inefficiencies and hinder the achievement of business goals. Implementing Enterprise Architecture (EA) using the Zachman Framework can play a role in helping overcome these challenges and maximizing the benefits of implementing information systems. This research aims to design an EA blueprint for machine distributor companies using the Zachman Framework mapping method. Data collection was carried out through interviews and observations to analyze the organization's value chain and develop scope, enterprise model and system model with a focus on data, function and network aspects. The results of this research produced a comprehensive and structured EA blueprint design, with a focus on three main aspects, namely data, function and network from the perspective of the owner and designer. This design is expected to help machine distributor companies achieve goals in the stock management process to increase data accuracy and operational efficiency